Whistle Blowing - A Paradigm Shift in Business Ethics - Kaur, Arvinder; Kaur, Baljinder (Prabandhan: Indian Journal of Management, 2011)
Whistle blowing is the disclosure by organizational members (former or current) of illegal, immoral or illegitimate practices under the control of their employers, to persons or organizations that may be able to affect the action. The revealed misconduct may be violation of a rule, law, regulation and/or a direct threat to the public interest such as fraud, health / safety violations and corruption. And if it is not disclosed, the silence may, however, pose a great threat to the society. Whistle blowing is significant as it often contributes to improvements in internal control system and provides solutions to organizational problems. Moreover, it is a sign of importance of the role of whistle blowers in the today’s society, where increasing emphasis is placed on ethical values in a direct response to corporate collapses.This paper examines the concept of whistle blowing and the costs and benefits associated therewith. Besides, the provisions of some of the laws and regulations to protect the whistle blowers have also been discussed. Some real cases from within India as well as outside India have been highlighted to support and justify the need for legal protection to the whistle blowers.